HRM effectiveness as a moderator of the relationships between abusive supervision and technology work overload and job outcomes for technology end users. Issue 8 (1st August 2013) - Harris, Kenneth J.; Lambert, Alysa; Harris, Ranida B.
Abstract Based on conservation of resources theory, this study examined the impact of two stressors: abusive supervision, an interpersonal stressor; and technology work overload, a contextual stressor, on job strain and perceived organizational support. These linkages have not been previously examined, but are of importance for managing employees who complete work on their computers. In a sample of 219 technology end users from a wide range of jobs and industries, we found that both of the stressors we examined had negative impacts on desired outcome variables. Additionally, we found that human resource management effectiveness moderated these relationships. These findings have important implications for theory and application which are discussed. Limitations and directions for future are also offered.